PEMANFAATAN SOLENOID VALVE DAN SENSOR HC-SR04 SEBAGAI PENCUCI TANGAN OTOMATIS BERBASIS ARDUINO UNO - Muhammad Furqon Siregar; Chairul Imam; Auliana Nasution (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2020)
The world is increasingly developing, along with the development of the times we have to explore ourselves, take advantage of existing technology for daily life. Technological developments are very rapid in various parties and any aspects. The world is now shocked by the corona virus disease, as if it reminds us to better save our health and save our immune system by take a rest and consume vitamins. Viruses that are currently being discussed can be prevented by saving our health, washing hands diligently, maintaining distance and avoiding crowds. Researchers took the initiative to look directly at the field where technology could be inserted in our healthy. From the results of research in the field, researchers found a problem in washing hands. Everyone, before or after washing their hands must be holding a soap bottle and water tap. It can cause new problems, which the virus can stick to the hands again through the water tap that the person had previously held. From the analysis of this problem, researchers want to make new innovations to prevent the spread of the Covid-19 virus. This innovation is a smart system design, where the system is integrated on its own without anyone's help. The work system uses sensors that are fully automatic. It is hoped that this tool can function and be applied to the society